Peran Konselor Dalam Pendidikan Karakter - El Fiah, Rifda (Universitas Islam Negeri Raden Intan Lampung, 2014)
Character education was one of the focuses in the system of national education. Therefore, educators must not neglect this. A school counselor, as one of the educators, has to play a role in character education. Referring to guidance and counseling responsibilities in relation to students’ personal, social, academic, and career aspects, a school counselor must not escape from the main duties. Considering that character education is the responsibility of all parties, a school counselor can, independently and in collaboration with all school components, play a role in character education. Individually, a school counselor can provide services, such as individual services, individual planning services, and responsive services. In collaboration with other parties, a school counselor can make a synergy in character education programs